2010
DOI: 10.1186/1471-2474-11-158
|View full text |Cite
|
Sign up to set email alerts
|

Maintaining a balance: a focus group study on living and coping with chronic whiplash-associated disorder

Abstract: BackgroundThere is little qualitative insight into how persons with chronic Whiplash-Associated Disorder cope on a day to day basis. This study seeks to identify the symptoms persons with Whiplash-Associated Disorder describe as dominating and explore their self-initiated coping strategies.MethodsQualitative study using focus groups interviews. Fourteen Norwegian men and women with Whiplash-Associated Disorder (I or II) were recruited to participate in two focus groups. Data were analyzed according to a phenom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
18
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 35 publications
(43 reference statements)
6
18
0
Order By: Relevance
“…It has been shown that those who expect severe symptoms after a musculoskeletal injury also use less adaptive coping strategies [23]. Given this finding, it may be that coping serves a key role in mediating the observed association between expectations for recovery (and possibly other pain-related beliefs) and actual recovery after a musculoskeletal injury [23][24][25][26][27].…”
Section: Implications For Rehabilitationmentioning
confidence: 97%
“…It has been shown that those who expect severe symptoms after a musculoskeletal injury also use less adaptive coping strategies [23]. Given this finding, it may be that coping serves a key role in mediating the observed association between expectations for recovery (and possibly other pain-related beliefs) and actual recovery after a musculoskeletal injury [23][24][25][26][27].…”
Section: Implications For Rehabilitationmentioning
confidence: 97%
“…Qualitative studies on coping among pain patients underscore the complexity of the strategies that the patients use. 57,88,89 One practical consequence of the idiosyncratic nature of coping is that psychologists who treat pain patients need to be sensitive to the ways in which individual patients construe their conditions and mobilize their coping resources to deal with them. The focus of psychologists on the idiosyncracies of beliefs and coping behaviors of patients stands in contrast to the focus of psychiatrists on placing patients into broad categories based on their DSM-5 diagnoses.…”
Section: The Psychological Perspectivementioning
confidence: 99%
“…Likewise, studies from 1983 4 and 2006 5 do not vary in their estimates that up to 30% of whiplash-injured individuals have persisting moderate to severe pain and disability, which may signifi cantly impact on their lives. 6 The trajectories of recovery and, importantly, nonrecovery refl ect the limited success of current treatments for acute whiplash, in particular for those individuals who transition to chronicity. 7 It was reasoned that if the rate of transition to chronicity was to be lessened, then it was time to gather experts together, think and refl ect collectively about the state of knowledge, assimilate observations across a spectrum of clinical and research disciplines, and consider new directions in research to drive forward the development and testing of new and innovative management approaches.…”
mentioning
confidence: 99%